Evaluación del comportamiento biológico de tres cementos obturadores endodónticos en tejido subcutáneo de ratones - Moraes, Sergio Herrero; Tanomaru Filho, Mario [UNESP]; Chavez-Andrade, Gisele Moraima [UNESP]; Silva, Guilherme Ferreira da [UNESP]; Tanomaru, Juliane Mario Guerreiro [UNESP] (My University, 2012)
The aim of this study was to evaluate the biological behavior of the root canal filling sealers: Endofill, Endomethasone and Sealer 26 when in contact with the subcutaneous connective tissue of rat. For the study one control and three experimental groups were used. A total of 15 animals were divided into 5 for each period: 7, 21, and 60 days. The obtained histological sections were processed and stained using the hematoxiline & eosine technique. The histological sections were subjective and comparatively analyzed using optic microscopy. The intensity of the inflammatory reaction and the level of fibrosis of the tissue were registered. The results were registered in scores and statistical analysis by KRUSKAL-WALLIS p<0,05 and MILLER methods. The statistical analysis revealed that in the period of 60 days, there was statistical significance to group II (Endofill) between group (control) and III (Endomethasone) with mononuclear cells into connective tissue. All materials promoted inflammatory reaction more intense at 7 and 21 days with the Endomethasone showing the best results.

El objetivo de este estudio fue evaluar el comportamiento biológico de los cementos endodónticos Endofill, Endomethasone y Sealer 26, en tejido conjuntivo subcutáneo de ratones. Fueron establecidos tres grupos experimentales y un grupo control de cinco animales cada uno, en los períodos de 7, 21 y 60 días. Los cortes histológicos obtenidos fueron coloreados con Hematoxilina & Eosina y con tricrómico de Masson, para posteriormente ser evaluadas la reacción inflamatoria adyacente y la formación de tejido fibroso. Los datos obtenidos fueron sometidos al test estadístico de Kruskall-Wallis y Miller con 5% de nivel de significancia. El análisis microscópico mostró reacción inflamatoria más intensa en los períodos de 7 y 21días. A los 60 días hubo formación de una cápsula fibrosa densa para el cemento Endomethasone y parcialmente densa para los demás cementos. El análisis estadístico mostró diferencia estadísticamente significativa con mayor intensidad de reacción inflamatoria solamente para el grupo II (Endofill) en el período de 60 días en relación a los grupos I (control) y grupo III (Endomethasone). Todos los materiales presentaron reacción inflamatoria más intensa en los períodos inicial e intermediario, siendo que la Endomethasone presentó los mejores resultados.
Keywords: Root canal obturation; Toxicity; Endodontic sealers; Obturación del conducto radicular; Biocompatibilidad; Cementos endodónticos